THE FORM AND THE FUNCTION THAT DEFINES AND ASSOCIATES DEFINITE AND INDEFINITE ARTICLES IN ENGLISH GRAMMAR (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Teachers expect that grammatical metadata is evidence-based, and not subject to inclusion of poetic license as is evident in Twain’s ‘The Prince and the Pauper’ novel, in which two characters are found to be identical in form (being thitherto unrecognized identically shaped twins) as well as being alike in function (they both manage to pass as royal princes in-waiting). But it must be asked, could similar poetic license have inadvertently found its way into the grammatical treatment of Articles? This question must be asked because past grammars have not used an evidence-based approach to describing Articles. To address this shortcoming, and believing that an analytical re-measurement is not out of place, this paper is confidant in proposing a substantial treatment of articles, which is based on kindred form and kindred function and not poetic license. The methodology of this paper, which is to employ discerning exemplars of English sentences, emulates three recent publications, the first of which concerned altering word prominence in pursuit of grammatical convenience; while the remaining papers were concerned with ESL mastery of the verb complex; and lastly, the decoding of contractions. Given that some ESL learners have never required (nor acquired) Articles in order to attain first language competency (say, for example, Czech and some Baltic languages), this paper will serve to shed new light on the hidden-in-plain-sight operations of English, and could become a source document for today’s ESL teachers on the treatment of Articles.